Qu yuan fang Sheng ta fei yin xiang = On the road: to Santa Fe - Ali Ginger 1970- (catch, 2021)
At the end of 2019, illustrator Ali Ginger set out for Santa Fe, New Mexico for a three-month residency that changed her outlook and her style. These three months offered rich and exciting stimulation and inspiration, starting from what happened in her layover in Japan. The continental landscapes of North America were so different from the tropical island of Taiwan, and she met interesting and friendly people from all over the world. These experiences changed her work as well. Both there and back home, new elements began appearing in her images. In this expansive and strange land, she rediscovered her passion for her work and her true self. The book includes a supplement of 20 sketches created during the artist’s residency. They are contained in an envelope, as if they were letters home. The simple drawings come with English captions written by the author, with the hope of conveying the artist’s true feelings in the moment.